Applications of Artificial Intelligence in Medicine. Analysis of Selected Case Studies - Bryś, Wojciech (Zastosowania sztucznej inteligencji w medycynie. Analiza wybranych studiów przypadków, 2025)
Artificial intelligence (AI) is a rapidly evolving field that has the potential to revolutionise industries, enhance human capabilities, and address complex societal challenges. This article provides an overview of the development of artificial intelligence. The article is divided into sections, focusing on literature review, technological foundations, legal and ethical dilemmas related to artificial intelligence, and practical aspects of artificial intelligence in medicine. Section 2 introduces artificial intelligence and provides an overview of technologies related to artificial intelligence. It also discusses ethical, economic, and technical perspectives. Section 3 explores the application of AI in medicine and healthcare institutions. The author’s personal contributions include critical analysis of AI’s technological principles, and a detailed discussion of its ethical dimensions. The author proposes tailor-made AI strategies for healthcare institutions, the aim of which is to maximise the quality of medical services and precise diagnostics while minimising the risks associated with the use of artificial intelligence.
Quote as: Bryś, W. (2024). Applications of Artificial Intelligence in Medicine. Analysis of Selected Case Studies. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 36-46). Publishing House of Wroclaw University of Economics and Business.
Keywords: artificial intelligence; AI in medicine; law and ethical AI; AI development trends; sztuczna inteligencja; AI w medycynie; prawo i etyka AI; trendy rozwoju AI